AN ANALYSIS OF ENGLISH TEACHER CHARACTER REFLECTED IN TEACHING LEARNING PROCESS: STUDENTS’ VIEWS IN IX GRADE AT MTS NURUL YAQIN - Memy Wardani Elthia (Graduate Program, University of Islam Malang, 2022)
This study aimed to know the character of the English teacher in IX grade IX of Mts Nurul Yaqin based on the student’s views. The subjects of this study are the students of Nurul Yaqin Junior High School, especially Students in grade IX. The method used in this study is descriptive qualitative and quantitative approaches to uncover the English teacher characteristics reflected in teaching and learning of English. The data collection involved some instruments namely questionnaire by Google Form and Interview using Voice Note feature in WhatsApp. The results of the study indicated that, most students had positive responses to the English teacher characters in IX grade of Mts Nurul Yaqin. It can be seen from the students' views that there is an English teacher in terms of professional competence and personality, among others, mastering the material 81,11% which means excellent, being patient, 79,25% meaning good, creative, 75,27% which means good, empathy 75,92% which means good. However, in terms of the utilizing of information and communication technology, the student's views are negative because it shows the value in the use of technology and communication in IX grade of an English teacher was 60,83% which means English teacher has fair character. Keywords: Teacher Characteristics, Concept of Teacher Character, Student views